Max Black on metaphorical language: exploring the line between analysis and aesthetics - Giuliani, Alice (Aesthetica Preprint, 2023)
This paper deals with Black’s philosophical proposal on metaphor as opening a threshold between analysis and aesthetics. Black was willing to show that analysis was adequate in explaining the cognitive and creative value of metaphor. But Black’s analysis also focused on innovation and metaphorical insight as aspects exceeding analytical skills and categories. Therefore, his interaction view is charged with aesthetic interest for two reasons: on the one hand, the method of analysis might have favoured the assimilation of metaphor to the conceptual metaphor of the cognitive approach; on the on the other hand, his studies provide the conditions to approach metaphor using aesthetic categories with greater critical awareness.